Case Study: Bipolar Disorder with Borderline Personality and Childhood Trauma - Suzy Yusna Dewi; Zikrina Istifarani; Yasmin Azizah Idhsa; Muthia Rahmah (Faculty of Medicine, UIN (State Islamic University) Syarif Hidayatullah Jakarta, 2022)
Background: Bipolar affective disorder is a mental disorder that is influenced by many factors, namely neurobiological factors and psychosocial factors. Due to these various factors, the outcome of bipolar affective disorder is different for each patient.Case report: One of the psychosocial factors that influence bipolar affective disorder is the presence of trauma in childhood and neglect. Trauma in childhood can be a precipitating factor in genetically predisposed individuals, triggering episodes of bipolar affective disorder as well as borderline personality disorder, also influencing the severity of symptoms and onset when the disorder first appearsResults:. The severity of bipolar symptoms is also greater in patients with a history of childhood trauma and neglect. This severity includes frequent suicidal ideation and the appearance of psychotic symptoms. Therefore, childhood trauma and neglect may be predictors of poor outcome in patients with bipolar affective disorder and the development of borderline personality disorder.